EVALUATION OF THE BEHAVIOUR OF DENTAL COMPOSITES RELATED TO DIFFERENT TYPES OF DRINKS BY THE DYNAMIC VAPOR SORPTION METHOD - Irina Gradinaru; Ana Lavinia Vasiliu; Alexandra Bargan; Bianca Iulia Ciubotaru; Adina Oana Armencia; Loredana Liliana Hurjui; Laura Elisabeta Checheriță; Cristina Gena Dascalu; Magda-Ecaterina Antohe (Romanian Society of Oral Rehabilitation, 2023)
Composite materials are biomaterials frequently used in dental restorations, offering an extremely wide range of structures adapted to both the location and the aesthetic and biomechanical requirements of the dental structure to which they are applied. The indications for the use of these biomaterials are not only restricted to the field of conservative dentistry but also in the preparation and reconstruction of dental structures involved in prosthetic therapy, periodontology and dental alveolar surgery, their choice being in accordance with the specifics of the operation performed. The aim of our study was to observe the influence of different beverage environment conditions on two types of obturation dental materials with different compositions from a morpho-structural point of view, water sorption characteristics of the restorative dental composites were determined through DVS measurements. By associating the value of isotherms with the degree of porosity of the surfaces of the two samples analysed, we can conclude that the surface alteration is relatively similar for the two types of material, with higher values being obtained for sample P1 in the presence of Red Bull and then Fanta.